Pengaruh Penggunaan Metode Inkuiri Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas IX SMP Negeri 1 Muara Batangtoru Tapanuli Selatan Tahun Pembelajaran 2023/2024 - Tirawati Siahaan; Simion Harianja; Senida Harefa (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to determine the positive and significant influence between the use of the inquiry method on the active learning of Christian Religious Education and Characteristics of class IX students of SMP Negeri 1 Muara BatangToru South Tapanuli for the 2023/2024 academic year. The research method used is a quantitative research method with inferential statistics. The population is all 102 class IX students of SMP Negeri 1 Muara BatangToru Tapanuli Selatan for the 2023/2024 academic year and the research sample was determined to be 36 people, which is 35% of the total population. Data was collected using a positive closed questionnaire with 36 items, namely 17 items for variable 1 Muara Batang Toru Tapanuli Selatan Academic Year 2023/2024: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.570 > rtable(a=0.05,n=36) = 0.329. b) Testing a significant relationship obtained a value of tcount= 4.040 > ttable(a=0.05, dk=n-2=34)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="29.04"+0.60X. b) Regression coefficient of determination test (r2) = 32.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=17, dk denominator=n-2=36-2=34) namely 16.31 > 1.62. Thus Ha, that is, there is a positive and significant influence of the use of the inquiry method on the learning activity of Christian Religious Education and Characteristics of class IX students of SMP Negeri 1 Muara Batang Toru South Tapanuli for the 2023/2024 academic year is accepted and H0 is rejected.